A new approach to valuing ecosystem services - Fogel, Daniel S. (Henry Stewart Talks, 2019)
This case study examines Belize’s unique response to rising sea levels. By valuing the services provided by coastal ecosystems and comparing the maintenance cost of these systems to the cost of building manmade structures that provide similar functions, Belize and Wake Forest University have developed a unique approach to supporting coastal communities and ecosystems.